From Qumran to the Yaḥad : a new paradigm of textual development for The community rule - Schofield, Alison. (Studies on the Texts of the Desert of Judah, 2009)
Since the discovery of the Cave 4 versions of The Community Rule (Serekh ha-Yaḥad or S), scholars have been perplexed about its complex textual history. This important charter material for the Dead Sea Scrolls' authors appears in alternate versions-ones with contradictory legal prescriptions and opposing self-references-but exhibits no clear order of chronological development. Benefitting from the entire Qumran library now available to us, this book offers a new, broader model for reading S that better accounts for the long and diverse history behind the text. The resulting paradigm challenges the Qumrancentric lens through which many read the "sectarian texts" and offers a fresh way of thinking about sectarian community formation among the authors of the Scrolls.